Role of the Central Bank in implementation of Value-Based Islamic Banking and Reporting in Bahrain – Exploring the challenges - Saeed Mohammed, Akhtar Ali; Mansor, Fadillah (European Journal of Islamic Finance, 2021)
This paper aims to explore the role of the Central Bank of Bahrain (CBB) in the implementation of Value-Based Islamic Banking (VBIB) and Reporting in Bahrain and explore the related challenges and provides suggestions that how the central bank can encourage the Islamic banks to align their operations for making a positive impact in society. The study employs a qualitative approach to understand the role of CBB in such implementation in Bahrain. The findings reveal that based on Islamic principles and Maqasid al-Shari’ah, CBB is yet to develop a strategy paper and framework for the value-based Islamic banking and reporting for the Islamic banking practices towards the well-being of the society and social objectives. As there has been very little written on value-based Islamic banking (VBIB) and reporting in Bahrain. Therefore, the study also adds value to the current Islamic finance literature and identifies the need for reporting standards to improve the VBIB practice in Bahrain in the future.